2015
DOI: 10.1108/ijilt-12-2012-0042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring students’ satisfaction with universities’ portals in developing countries

Abstract: Purpose – The purpose of this paper is to investigate the factors affecting students’ satisfaction with university portals in developing countries. The factors examined are educational services availability, user ability, system quality and information quality. Design/methodology/approach – A self completion questionnaire was developed and distributed to a sample of 550 students in several universities. Correlation and regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 22 publications
6
28
0
3
Order By: Relevance
“…This research states that the quality teaching system provided by the Faculty of Economics is able to deliver faculty students' satisfaction. This study is in line with the research of Shaltoni et al, [17] which states the provided quality system bringing impacts on faculty students' satisfaction. This research is also in line with Martirosyan [18], which states the education system related to faculty services, academic experience, student support facilities, campus life, and social integration bringing influence to students' satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…This research states that the quality teaching system provided by the Faculty of Economics is able to deliver faculty students' satisfaction. This study is in line with the research of Shaltoni et al, [17] which states the provided quality system bringing impacts on faculty students' satisfaction. This research is also in line with Martirosyan [18], which states the education system related to faculty services, academic experience, student support facilities, campus life, and social integration bringing influence to students' satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…According to Khasawneh (2015), Jordan adopted the use of ICT in all sectors including higher education institutions and universities as part of its strategy to overcome its lack of provision. Jordan has invested in higher education with the establishment of over 30 universities (Al-Sarayreh & Al-Assaf, 2008).Many studies has addressed the quality factors of Jordanian universities websites and e-services portals such as the study conducted by Awwad (2006) which studied the quality factors of Jordanian universities websites; the study of Shaltoni et al (2015) whom explored the students satisfaction with universities portals in developing countries. Moreover, Hasan conducted a Heuristic Evaluation of Three Jordanian Universities websites and before that, she evaluated the usability of nine Jordanian universities websites (Hasan, 2013).…”
Section: Situation In Jordanmentioning
confidence: 99%
“…Research variables are all conditions that are observed to be controlled and even manipulated by the researcher when conducting research (Cohen, Huprich, Jones, & SMith, 2015). The Directorate of Higher Education, the ministry of education and culture defines it as all things that are used as objects in research.…”
Section: Methodsmentioning
confidence: 99%